Penggunaan model pembelajaran kooperatif tipe think pair share untuk meningkatkan kemampuan menganalisis unsur-unsur puisi kelas IV sekolah dasar - Fitri Rahmawati Nugraha; Retno Winarni; Tri Budiharto (Didaktika Dwija Indria, 2019)
Abstract..This research aims to improve the ability to analyze poetry elements by implementing cooperative learning model type Think Pair Share in IV grade students of Public Elementary Shcool Ngoresan No. 80 Jebres Year 2018/2019. This research was a Classroom Action Research conducted in two cycles. Each cycle had four stages namely planning, implementation, observation and reflection. The subject of this research were 31 IV grade students. The data of this research were collected using test, interview, observation, and documentation technique. The data were analyzed using interactive analysis technique which consisted of data collection, data reduction, data presentation, and conclusion.The pre-action results show that the students’ average ability to analyze poetry is 59.63 with a classical completeness percentage of 23% who can reach minimal completeness criteria (75). The results of cycle I show that the average ability to analyze poetry improves to 62.93 with a classical completeness percentage of 43%. The results of cycle II show that the average ability to analyze poetry also improves to 80.13 with a classical completeness percentage of 81%.    The conclusion of this research is that the implementation of cooperative learning model type Think Pair Share can improve the ability to analyze poetry elements in the IV grade students of Public Elementary Shcool Ngoresan No. 80 Jebres.Keywords: ability,analyzing the elements of poetry, cooperative learning model type think pair share, elementary school